Penyuluhan Pemanfaatan Limbah Kulit Buah Nanas Sebagai Alternatif Pembuatan Sabun Cuci Piring Di Kelurahan Bukit Pinang, Samarinda, Kalimantan Timur - Muhammad Nuzul Azhim Ash Siddiq; Baso Didik Hikmawan; Hajrah; Noviyanty Indjar Gama; Nur Masyitah Zamruddin; Akhmad Jaizzur Rijai; Viriyanata Wijaya (CV. Multi Kreasi Media, 2023)
Domestic waste is a global problem that is growing along with population growth and changes in consumption patterns. Domestic waste, if not handled properly, can cause environmental and health problems. Pineapple peel as a type of domestic waste has the potential to be used as an alternative pharmaceutical product because it still contains compounds in it, such as enzymes and bioactive compounds. Utilizing this waste not only reduces negative impacts on the environment, but also creates high-value products that are beneficial to society. Utilizing pineapple peel waste as a dishwashing soap product is the focus of our community service. The use of fruit peel waste represents a progressive step towards sustainability, small-scale home industry innovation and waste reduction which are increasingly important in efforts to preserve the environment and create products that are more beneficial to humans.